PILKADES DAN JARINGAN KEKERABATAN Studi Kasus Desa Susukan Kecamatan Comal Kabupaten Pemalang Jawa Tengah - , Dyah Rahayuningtyas, Dr. Bambang Hudayana ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Pilkades (village headman election) is a phenomenon of local politic as a form of democracy in Indonesian government. Village headman is a precious position among the villagers. In some area, pilkades often becoming an arena of competition between elite, both in a group and individual. That elites were fought for power and strength in order to affect society based on two forces: basic power of material and non material. Basic power of materials consist of land ownership and possession of money, while basic power of non materials consist of locality, social-religious, and kinship networks. This study observed the role of kinship networks in Pilkades contestation in Susukan Village, Comal Distric, Pemalang-Central Java. This study showed that pilkades was quite tight as characterized by elite competition. The election showed that the role of kinship networks has a significant power. The winner was laid his power and authority in large amount of kinship networks. In fact, kinship networks showed a significant power to defeat material power. It showed a contrast between democracy system which the winner hold on accountability, quality, and capability, and paternalistic system which the winner hold on the power of kinship networks. They were faced one and other. However, a democracy system can walk s together with paternalistic system which was risen first in Javanese society. This study was done in Susukan Village, Comal Distric, Pemalang-Central Java. The metods of the riset were observation participation (before, during, and after pilkades), and interview with open questions (but still focus on the topic). The result of the riset was analized with descriptif analysis on qualitative data which come from observation, interview, and literature.